Effectiveness of the program of physical rehabilitation for persons with gunshot fractures of the proximal humerus - Ostroushko, Oleksandra; Kalinkin, Kostiantyn (Journal of Education, Health and Sport, 2017)
In connection with the events taking place in Ukraine, there is an urgent need to develop modern rehabilitation measures for the restoration of health and efficiency of persons with fire-fighting lesions of various degrees of gravity. The analysis of literary sources regarding military conflicts shows the prevalence of firearms of extremities 70%, shoulder bone damage 22.3%. Gunfire is a multicomponent stress that results in a disruption of the vital organs and body systems. Purpose: To analyze the dynamics of indicators of sociological and clinical and instrumental methods of research of patients with gunshot fractures of the proximal humerus division under the influence of a comprehensive program of physical rehabilitation. Methods of research: analysis of special scientific and methodical literature; sociological and clinical and instrumental research methods. Results. The features of the functional and psycho-neurological state of the military, which determine the orientation of the rehabilitation process and its components, are determined by kinesiotherapy, PNF therapy, motor training, Thera-band advanced therapy exercises, physiotherapy, vibrotherapy and mechanotherapy, aimed at improving the functional state of patients. After application of the proposed program of physical rehabilitation, reliable positive changes of the studied indicators were revealed. Conclusions. Experimental testing of the developed program of physical rehabilitation has shown its effectiveness, which manifests itself in improving the functional and psycho-neurological status of servicemen.